The Chinese and Russian Strategies in the Shanghai Cooperation Organization: Comparative Analysis - Li Xing (Сравнительная политика)
The Shanghai Cooperation Organization (SCO) was established at the beginning of the XXI century as a new regional intergovernmental organization that embraces such crucial spheres of international relations as security, politics and humanitarian ties. The members-states are economies with transition and developing countries of Central Eurasia.Being the drivers of the organization, China and Russia have signifi cant infl uence on the SCO. From this perspective, comparing Chinese and Russian strategies in the Shanghai Cooperation Organization remains an issue of interest both theoretically and practically